The social network - Ficher, David; Eisenberg, Jesse; Garfield, Andrew; Timberlake, Justin; Columbia Pictures (California : Columbia Pictures Industries, Inc., 2010)
The Social Network is the stunning tale of a new breed of cultural insurgent: a punk genius who sparked a revolution and changed the face of human interaction for a generation, and perhaps forever. Shot through with emotional brutality and unexpected humor, this superbly crafted film chronicles the formation of Facebook and the battles over ownership that followed upon the website's unfathomable success.
Disc 1. The film -- Disc 2. The supplements.
Based upon the book'The accidental billionaires' by Ben Mezrich.
Editors, Angus Wall, Kirk Baxter ; music by Trent Reznor, Atticus Ross ; director of photography, Jeff Cronenweth ; executive producer, Kevin Spacey.
Jesse Eisenberg, Andrew Garfield, Justin Timberlake, Armie Hammer, Max Minghella.
LPF: 18
DVD format, Anamorphic widescreen (2.40:1), Region 3, Dolby Digital.
In English, Potugese, Thai with optional English, English SDH (deaf or hard-hearing), Portugese (Portugese subtitled commentary), Thai, Chinese traditional, Korean subtitles.
Keywords: Zuckerberg, Mark, -- 1984- -- Drama; Facebook (Firm) -- Drama; Biographical films; Social network -- Drama